Characterization Of Oil Palm Shell Nano Filler In Hybrid Kenaf/Coconut Fibres Reinforced Polyester Composites - Wan Othman, Wan Nornadirah (2014)
In this research, hybrid kenaflcoconut fibres reinforced polyester composites were developed and enhanced with nano filler Oil Palm Shell (OPS). The raw OPS was subjected to grinding followed by high-energy ball milling for 30 hours to become OPS nano particles. Characterization of OPS nano filler such as surface morphologies, elemental composition and functional groups were evaluated by using Scanning Electron Microscopy equipped with Energy Dispersive X-ray Analysis (SEM with EDX), Fourier Transform Infrared Spectroscopy (FT-IR) respectively. The SEM-EDX images revealed that OPS nano filler produced consisted of crushed and irregular shape structures with presence of carbon and oxygen as a major elements composition. Besides, Transmission Electron Microscope (TEM), X-ray Diffraction (XRD) and Thermogravimetric Analysis (TGA) were used to characterize particle size, crystallinity index and thermal properties of OPS nano filler respectively. The TEM micrograph revealed that OPS particles size ranged between 10 to 30 nm indicates their nanometric nature.